Modeling and optimization of artificial magnetic conductor on the performance of on-chip-antenna for 28 GHz devices - Ahmadu Girgiri; Mohd Fadzil Ain; Mohd Zamir Pakhuruddin; Mohamad Faiz Mohamed Omar; Bello Muhammad Abdullahi (Universitas Ahmad Dahlan, 2024)
The growing popularity of chip-based devices has spurred interest in developing on-chip antennas (OCAs). However, low gain and poor radiation characteristics have been significant challenges. Integrating an artificial magnetic conductor (AMC) into the oxide layer is an alternative. This article presents a new AMC model that improves the performance of 28 GHz OCA using dual-rectangular-patch (DRP) as unit cells. The DRP parameters, patch width (Pw), patch gap (Pg), and substrate height (hs) were used to control the AMC characteristic. Two numerical equations for gain (G) and efficiency (η) have been developed to evaluate the new model’s performance. The impact of parameters on the antenna’s gain and radiation efficiency was equally analyzed. A prototype antenna was fabricated and tested to validate the model. It demonstrated a peak gain of 3.69 dB and radiation efficiency of 67.18%, with an achieved impedance bandwidth of 1.27 GHz, making it well-suited for 28 GHz device applications. Furthermore, the equations formulated provide the research community with a straightforward method to calculate the gain and efficiency of a 28 GHz antenna. This method is not limited to on-chip antennas but can also be applied to off-chip antennas if DRP-AMC is implemented.